Influence of pedestrian grouping on evacuation efficiency in underground flooded stairs: a 3D numerical assessment - Carlos H. Aparicio Uribe; Beniamino Russo; Jackson Téllez-Álvarez; Eduardo Martínez-Gomariz (Progress in Disaster Science, 2025)
Urban floods increasingly threaten underground spaces and their users. Often essential for evacuation, stairs pose unique challenges as they also serve as the main path for the incoming water. While prior studies typically examine individual behaviour, the role of groups on flooded stairs remains underexplored. This study addresses that gap through a 3D numerical analysis evaluating how different pedestrian arrangements affect evacuation efficiency and safety. Using realistic human body dummies on real-scale stairs under a water discharge of 0.423 m3/s, the analysis calculates hydrodynamic forces alongside Momentum of Flow MF and Specific Force Per Unit Width (SFPUW) M0 to assess hazardous conditions. Scenarios include individuals alone, in tandem, and side-by-side. Results show that group configurations significantly influence water-dragging forces. Side-by-side arrangements increased the force on both neighbouring and downstream pedestrians, while tandem formations reduced drag on trailing individuals. Greater separation distances between individuals reduced force influences. These findings reveal how group positioning affects safety during evacuation and highlight potential bottlenecks. The study offers valuable insights for improving evacuation strategies and safety protocols in underground infrastructure during floods, ultimately contributing to urban resilience and effective flood risk mitigation.